A Reusable Software Copy Protection Using Hash Result and Asymetrical Encryption - Wibisurya, Aswin; Adinugroho, Timothy Yudi (Bina Nusantara University, 2014)
Desktop application is one of the most popular types of application being used in computer due to the one time install simplicity and the quick accessibility from the moment the computer being turned on. Limitation of the copy and usage of desktop applications has long been an important issue to application providers. For security concerns, software copy protection is usually integrated with the application. However, developers seek to reuse the copy protection component of the software. This paper proposes an approach of reusable software copy protection which consists of a certificate validator on the client computer and a certificate generator on the server. The certificate validator integrity is protected using hashing result while all communications are encrypted using asymmetrical encryption to ensure the security of this approach.